Assessment of the effects of mental health training on barangay nutrition scholars in Quezon City - Quesada, Minda Luz M. (1990)
This exploratory study attempted to 1) train indigenous lay community workers--the Barangay Nutrition Scholars of Quezon City-- in primary mental health care; 2) evaluate the effects of training on their knowledge, attitudes, values, and skills; 3) identify the stressful life events commonly experienced by client families of BNS; and 4) ascertain the influence of selected sociodemographic background characteristics on the effect of the educational intervention. This quasi-experimental study used the non-randomized control group pretest-posttest research design. 41 BNS took part in the study, which was conducted in densely populated and depressed communities, 20 of which constituted the experimental group while 21 made up the control group. The experimental group was exposed to a 5 half-day primary mental health training program while the control group went through a 5 half-day placebo training program (health education). The main evaluation instrument used was the pre- and posttest questionnaire--consisting of items on knowledge, attitudes, values, and skills--which was administered immediately before and after the training program. Evaluation of the field performance of the BNS was made 2 months after training using anecdotal records/reports of the BNS that in turn were validated by field researchers. This was aimed at ascertaining the ability of the BNS to 1) identify individuals in their client families who were undergoing stressful life events, and 2) provide social support to them. A total of 410 families were interviewed/observed by the BNS, 200 in the treatment group and 210 in the control group. The same household respondents were also interviewed by the field researchers.